2021
DOI: 10.1186/s12887-020-02458-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of FIBEROPTIC phototherapy compared to conventional phototherapy in treating HYPERBILIRUBINEMIA amongst term neonates: a randomized controlled trial

Abstract: Background Neonatal jaundice is one of the most common problems in neonates. Effective treatment of jaundice requires therapeutic intervention with high quality phototherapy. Over recent years, several studies reported fiberoptic phototherapy to be less effective than conventional phototherapy in term neonates. Our study aimed to compare the effectiveness of fiberoptic phototherapy with a larger illuminated area and higher irradiance to conventional phototherapy methods. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
10
0
3
Order By: Relevance
“…We evaluated 41 full-text articles to check for eligibility, and, ultimately, 21 were included in this review. 3,15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The flowchart for evidence search and study selection is shown in ►Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated 41 full-text articles to check for eligibility, and, ultimately, 21 were included in this review. 3,15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The flowchart for evidence search and study selection is shown in ►Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…15,[23][24][25] Fifteen articles compared LED devices with fluorescent lights. 3,[26][27][28][29][31][32][33][34][35][36][37][38]40,41 Two studies compared LED devices with halogen and fluorescent lights. 30,39 Five studies enrolled only full-term neonates 15,23,38,40,41 and 13 studies included infants over 35 or 36 weeks of gestation.…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analysis based on the risk of bias was done in order to lower the heterogeneity between the studies on phototherapy duration outcome. Lowering the phototherapy duration might lower the phototherapy exposure, side effects, hospitalization, and cost [ 32 ]. Phototherapy may have some side effects, but some of these are more common in conventional phototherapy devices, for example by using fluorescent tubes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…No artigo desenvolvido por Joel et al (2021), foi comparado a eficácia da fototerapia com fibra óptica, também chamada de fiberoptic, com maior área iluminada e maior irradiância aos métodos convencionais de fototerapia. Os resultados mostraram que houve diferença estatisticamente significativa na taxa geral de redução de bilirrubina entre a fototerapia convencional de fibra óptica e luz branca, entretanto, não houve diferença estatisticamente significativa quando comparado a taxa geral de redução de bilirrubina entre luz azul de fototerapia convencional e fibra óptica.…”
Section: Análise Dos Estudosunclassified